Hierarchical Graphical Bayesian Models in Psychology - Guillermo Campitelli (Revista Colombiana de Estadística, 2014)
The improvement of graphical methods in psychological research can pro- mote their use and a better comprehension of their expressive power. The application of hierarchical Bayesian graphical models has recently become more frequent in psychological research. The aim of this contribution is to introduce suggestions for the improvement of hierarchical Bayesian graphical models in psychology. This novel set of suggestions stems from the descrip- tion and comparison between two main approaches concerned with the use of plate notation and distribution pictograms. It is concluded that the combi- nation of relevant aspects of both models might improve the use of powerful hierarchical Bayesian graphical models in psychology.